2017
DOI: 10.1186/s12888-017-1486-9
|View full text |Cite
|
Sign up to set email alerts
|

Family-based intervention in adolescent restrictive eating disorders: early treatment response and low weight suppression is associated with favourable one-year outcome

Abstract: BackgroundFamily-based treatments are first-line treatments for adolescents with restrictive eating disorders (ED) but have to be improved since outcome is poor for some. We have investigated the one-year outcome of a family-based intervention programme with defined and decisive interventions at the start of treatment.MethodData pertaining 201 adolescents with restrictive ED with features of anorexia nervosa but not fulfilling the weight criterion starting treatment 2010-2015, had a wide range of body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 55 publications
(63 reference statements)
5
20
0
1
Order By: Relevance
“…Moreover consistently with the present study, several studies have shown that WS may not be associated with treatment outcome such as binge/purge abstinence, response, remission, in patients with BN (Carter et al, 2008;Dawkins et al, 2013;Zunker et al, 2011), nor with treatment compliance or drop-out rates (Carter et al, 2008). On the other hand, other evidence suggests a role of WS in determining clinical outcome (Butryn et al, 2011;Swenne, Parling, & Salonen Ros, 2017), included maintenance of bulimic syndromes (Keel & Heatherton, 2010), resumption of menses (Seetharaman et al, 2017), at follow-up as long as 20 years (Bodell, Brown, & Keel, 2017;Witt et al, 2014). Notably, we originally also show that WLS is associated with a better prognosis, suggesting that rapidly evolving clinical pictures may have a favorable outcome compared with those with insidious onset.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover consistently with the present study, several studies have shown that WS may not be associated with treatment outcome such as binge/purge abstinence, response, remission, in patients with BN (Carter et al, 2008;Dawkins et al, 2013;Zunker et al, 2011), nor with treatment compliance or drop-out rates (Carter et al, 2008). On the other hand, other evidence suggests a role of WS in determining clinical outcome (Butryn et al, 2011;Swenne, Parling, & Salonen Ros, 2017), included maintenance of bulimic syndromes (Keel & Heatherton, 2010), resumption of menses (Seetharaman et al, 2017), at follow-up as long as 20 years (Bodell, Brown, & Keel, 2017;Witt et al, 2014). Notably, we originally also show that WLS is associated with a better prognosis, suggesting that rapidly evolving clinical pictures may have a favorable outcome compared with those with insidious onset.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover consistently with the present study, several studies have shown that WS may not be associated with treatment outcome such as binge/purge abstinence, response, remission, in patients with BN (Carter et al, ; Dawkins et al, ; Zunker et al, ), nor with treatment compliance or drop‐out rates (Carter et al, ). On the other hand, other evidence suggests a role of WS in determining clinical outcome (Butryn et al, ; Swenne, Parling, & Salonen Ros, ), included maintenance of bulimic syndromes (Keel & Heatherton, ), resumption of menses (Seetharaman et al, ), at follow‐up as long as 20 years (Bodell, Brown, & Keel, ; Witt et al, ). Several factors may underlie such discrepancies about the role of WS in determining clinical outcomes, included the population on which outcomes are measured (completers vs. intention‐to‐treat), diagnostic criteria defining EDs (DSM‐IV vs. DSM‐5 vs. subthreshold syndromes), covariates considered in the analyses (adjusted vs. unadjusted analyses), and WS calculation (weight [kg] vs. BMI).…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been well established that early weight gain within the first 4 weeks of treatment is strongly linked to an increased probability of success in FBT (Doyle et al, 2010;Le Grange et al, 2014;Madden et al, 2015;Swenne et al, 2017), in addition to the potential for family burnout and diminished quality of life associated with longer treatment duration, this profile might represent a subset of adolescents who would ultimately benefit from more intensive or adapted interventions, but who advance-albeit more slowly-in FBT. Without outcome data, it is unclear whether this class is associated with treatment success or failure, though the group had significantly more patients fail to reach an early weight gain cut-off point of 6.5 pounds in 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Without outcome data, it is unclear whether this class is associated with treatment success or failure, though the group had significantly more patients fail to reach an early weight gain cut-off point of 6.5 pounds in 4 weeks. Because it has been well established that early weight gain within the first 4 weeks of treatment is strongly linked to an increased probability of success in FBT (Doyle et al, 2010;Le Grange et al, 2014;Madden et al, 2015;Swenne et al, 2017), in addition to the potential for family burnout and diminished quality of life associated with longer treatment duration, this profile might represent a subset of adolescents who would ultimately benefit from more intensive or adapted interventions, but who advance-albeit more slowly-in FBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation